Fluorinate polyacrylic acid and its use as a potential adjuvant field - Bai Lu; Li Chengyu; Zhou Mengmeng; Chen Xiaoqi; Zhou Haijun; Zhang Fen; Li Xin; Li Yantao (BIO Web of Conferences, 2022)
This study describes a polymer potentially used as a vaccine adjuvant. We first synthesized a novel polyacrylic acid modified by perfluorinated butanol—a bioactive compound that is biocompatible. The main aim was to functionalize the polyacrylic acid by fluorine. This functionalization could offer a permanent graft by an esterification reaction. The chemical structure of the polymer has been characterized by the hydrogen nuclear magnetic resonance spectrum (1H-NMR) and fourier transform infrared spectrum (FT-IR). Thermal analysis showed that the esterification reaction was successful on the polyacrylic acid. Viscosity testing showed that the viscosity of the sample aqueous solution increases along with esterification. The surface tension of the polymer was also tested. The results show that the surface tension of the polyacrylic acid markedly decreased when modified by fluorine. Finally, the interaction of these materials with macrophages was tested on cell test. Results showed that the modified polyacrylic acid performed better improve the activation effect than pure polyacrylic acid in 1L-1β.